Rationalitation of the Organization of the Local Russian Self-Government. /Racionalización de la organización del autogobierno local ruso. - FAATOVNA NIGMATULLINA, ELMIRA; AIDAROVNA ZALIALETDINOVA, DIANA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to the organization of local self-government in the context of the search for new rationality. Moving on to the individual powers of local self-government bodies, the authors discuss the need to modernize management in municipalities, which is designed to guarantee every citizen the right to participate in the implementation of local self-government. In relation to the main functions of local self-government bodies contained in the legislation (in ensuring a favorable environment, collective actions), the authors give judicial practice as an example and identify problems of law enforcement, stated in the final part of the work. RESUMEN El artículo está dedicado a la organización del autogobierno local en el contexto de la búsqueda de una nueva racionalidad. Pasando a los poderes individuales de los órganos de autogobierno local, los autores discuten la necesidad de modernizar la gestión en los municipios, que está diseñada para garantizar a todos los ciudadanos el derecho a participar en la implementación del autogobierno local. En relación a las principales funciones de los órganos de autogobierno local contenidas en la legislación (en asegurar un entorno favorable, acciones colectivas), los autores dan como ejemplo la práctica judicial e identifican problemas de aplicación de la ley, expresados en la parte final del trabajo.